Effect of Phytophasic Irrigations on Growth Yield and Water Use in Linseed - Yusuf, Mohd; Sadaphal, M N; Singh, M N; Dastane, N G (Annals of Arid Zone, 2016)
In a two year (1970-72) field study linseed (Linum usitatissimum L.) was irrigated at frequencies varying from I to 4 at different phytophases. An unirrigated plot was included as a check. Irrigation at seedling stage was found to be the most critical followed by the one at flowering. Yield obtained in different frequencies increased with the increase in number of irrigations. Oil content of seed was not affected by either the stage or the frequency of irrigation. Consumptive water use increased with the frequency of irrigation. Water use efficiency was highest under treatments involving one irrigation and decreased with an increase in frequency. Soil moisture extraction in general, decreased with an increase in profile depth and was more from lower depths in respect of low frequencies.